A Comprehensive Review of the Use of Nanoparticles in Cosmeceutical Science: Review Article (Journal of Pharma Insights and Research, 2024)
Nanotechnology is significantly impacting the cosmeceutical sector, revolutionizing how skincare products are formulated and delivered. Innovative nanoparticle delivery systems such as liposomes, niosomes, nanostructured lipid carriers (NLCs), solid lipid nanoparticles (SLNs), gold nanoparticles, and nano-emulsions are at the forefront of this transformation. These systems enhance the bioavailability, stability, and efficacy of active ingredients, offering controlled release and targeted delivery features that are crucial for optimizing cosmetic results. Nanotechnology facilitates improved penetration of actives into the skin, protects ingredients from degradation, and ensures sustained release, thereby enhancing the therapeutic effectiveness of cosmeceuticals. Additionally, the integration of nanoparticles into cosmetic products allows for reduced dosages and minimized side effects, which contributes to better skin tolerance and safety. However, the use of nanotechnology in cosmeceuticals is not without challenges. It raises significant safety and environmental concerns due to the potential systemic absorption of nanoparticles. Regulatory bodies globally are striving to address these issues, with guidelines and regulations continuously evolving to ensure consumer safety while fostering innovation. The current review highlights the dual aspects of opportunity and oversight that nanotechnology brings to the beauty and skincare industry, emphasizing the need for ongoing research and regulatory vigilance to harness its full potential responsibly